A phase I, randomized, double‐blind study to assess the safety, tolerability and efficacy of the topical RORC2 inverse agonist PF‐06763809 in participants with mild‐to‐moderate plaque psoriasis. (14th September 2020) - Berstein, G.; Zhang, Y.; Berger, Z.; Kieras, E.; Li, G.; Samuel, A.; Yeoh, T.; Dowty, H.; Beaumont, K.; Wigger‐Alberti, W.; von Mackensen, Y.; Kroencke, U.; et al.
Summary: Background: Transcription factor retinoic acid‐related orphan receptor 2 (RORC2/RORγT) mediates interleukin (IL)‐17A and IL‐17F expression. IL‐17A plays a central role in the pathogenesis of several inflammatory disorders, including psoriasis. The RORC2 inhibitor PF‐06763809 has been hypothesized to inhibit IL‐17A production in T‐helper 17 (Th17) cells, thereby reducing psoriasis symptoms. Aim: To assess the safety, tolerability and effect on skin infiltrate thickness of PF‐06763809 in participants with mild/moderate chronic plaque psoriasis. Methods: This was a randomized, double‐blind, first‐in‐human study (trial registration: ClinicalTrials.gov NCT03469336). Participants received each of the following six treatments once daily for 18 days: three topical doses (2.3%, 0.8%, 0.23%) of PF‐06763809, a vehicle and two active comparators (betamethasone and calcipotriol). Primary endpoints included change from baseline in psoriatic skin infiltrate thickness [echo‐poor band (EPB) on ultrasonography] at Day 19, and safety. Change in psoriasis‐associated gene expression (Day 19), evaluated by real‐time reverse transcription PCR of skin biopsies, was an exploratory endpoint. Results: In total, 17 participants completed the study. Change from baseline in the EPB on Day 19 for all three doses of PF‐06763809 was not significantly different from that of vehicle ( P > 0.05). A significant reduction in EPB from baseline was observed with betamethasone on Day 19 relative to all other treatments ( P < 0.0001). Treatment‐related adverse events were mild/moderate. There were no significant differences in gene expression on Day 19 between vehicle and PF‐06763809‐treated skin lesions. Conclusion: Using a psoriasis plaque test design, PF‐06763809 was found to be well tolerated with an acceptable safety profile in participants with psoriasis, but without reduction in skin infiltrate thickness or disease biomarkers.